A cidade, seus muros e suas leis: controvérsias jurídicas e urbanísticas dos condomínios e loteamentos fechados - Raquel Tomanik (2020)
Gated communities are controversial figures in urban development, mainly due to their imprecise placement in federal legislation and the fact that they cause social segregation, blocking access to public spaces and dispersed urbanization. Despite its long existence in Brazilian cities, as well as the extensive academic debate regarding the inadequacy of the model as an alternative to traditional land parceling patterns, the regulation of these enterprises was introduced suddenly, and in a succinct way, in the federal legislation recently in 2017 – with the approval of Federal Law 13.465 (REURB Law). The mismatch between urban regulation and space production gives this type of real estate development a conflicting position in relation to the city and the law. Aiming to unveil this condition, this research has as its theme the regulation of gated communities exploring their legal and urban controversies. For this, the relationship of these “exclusive neighborhoods” with urban expansion/dispersion and metropolization processes is studied, as well as with impacts on the land valorization when there is a change in legislation to make them possible. Legal controversies are analyzed based on the historical rescue of the rules applied to land parceling in Brazil, until the brief mention of the closed projects in the federal regulation. Then, the urban controversies of these enterprises are examined considering precepts of the social function of property and principles of the just city enumerated by Fainstein (2010): equity, diversity and democracy. Subsequently, the Municipality of Betim/MG is contextualized – as an empirical case to illustrate the types of feasibility of the “city inside the walls” – exposing the characteristics of its territorial organization, urban laws (especially that applied to the land parceling) and management of local urban policy. The final considerations of this thesis debate the future of the “city outside the walls”, which is increasingly segregated and dispersed, gathering guidelines for a possible insertion of gated communities in the urban context.